Pengembangan Bahan Ajar Matematika Menggunakan Kvisoft Flipbook Maker Materi Perbandingan Siswa Kelas VII - Palenita Repi; Derel F. Kaunang; Rosiah J. Pulukadang (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2022)
The purpose of this research is to examine whether the comparison teaching materials developed through Kvisoft Flipbook Maker can help the learning process at Woloan Christian Middle School. The researcher uses R&D (Research and Development) research model with research methods based on Sugiyono's theory, namely there are seven stages of development, potential, and problems, data collection, product design, design validation, design revision, product testing, and product revision. This teaching material contains interesting animations, audio, and video that can motivate students in learning and is also expected to make it easier for students to understand the comparison material. The results showed that the teaching materials developed were suitable for use in teaching and learning activities. The assessment was carried out using three experts and obtained percentages of 93%, 89%, and 88% so that it met the validity aspect. The responses of teachers and students on the use of teaching materials are very good with a percentage of 93% and 87% so that they meet the practical aspect. Learning outcomes obtained based on testing of 34 seventh grade students of Woloan Christian Middle School were very good with a completeness percentage of 82% and met the effectiveness aspect. Keywords: teaching materials, kvisoft flipbook maker, comparison The purpose of this research is to examine whether the comparison teaching materials developed through Kvisoft Flipbook Maker can help the learning process at Woloan Christian Middle School. The researcher uses R&D (Research and Development) research model with research methods based on Sugiyono's theory, namely there are seven stages of development, potential, and problems, data collection, product design, design validation, design revision, product testing, and product revision. This teaching material contains interesting animations, audio, and video that can motivate students in learning and is also expected to make it easier for students to understand the comparison material. The results showed that the teaching materials developed were suitable for use in teaching and learning activities. The assessment was carried out using three experts and obtained percentages of 93%, 89%, and 88% so that it met the validity aspect. The responses of teachers and students on the use of teaching materials are very good with a percentage of 93% and 87% so that they meet the practical aspect. Learning outcomes obtained based on testing of 34 seventh grade students of Woloan Christian Middle School were very good with a completeness percentage of 82% and met the effectiveness aspect. Keywords: teaching materials, kvisoft flipbook maker, comparison